Motivation Behind Writing Fanfictions for Digital Authors on Wattpad and Twitter - Ario Budiarto; Rizki Chairunissa; Annisa Fitriani (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
Fandom culture has emerged a new culture called fanfictions where fans create a fictional story based on the popular culture they like. An example of the most common cultures being made into fanfictions is K-pop. Nowadays, K-pop fanfictions can be seen almost everywhere, especially in digital platforms, like Wattpad and Twitter. Therefore, this research aims to analyze the motivations of the digital authors in writing fanfictions on Wattpad and Twitter through structuralist approach. After interviewing the authors and analyzing those interviews, the finding shows that the biggest motivation came from the love of K-pop culture itself, specifically idol culture as through writing fanfictions, they feel to have a special relation with the idols. Meanwhile, digital platforms here also have an important role in giving feedbacks to the author which also give them a boost of motivation.